Acute Stress Facilitates LTD Induction at Glutamatergic Synapses in the Hippocampal CA1 Region by Activating μ-Opioid Receptors on GABAergic Neurons - Fan, Ka-Min; Qiu, Li-Juan; Ma, Ning; Du, Yi-Nan; Qian, Zhao-Qiang; Wei, Chun-Ling; Han, Jing; Ren, Wei; Shi, Mei-Mei; Liu, Zhi-Qiang (Frontiers in Neuroscience, 2019)
Acute stress impairs recall memory through the facilitation of long-term depression (LTD) of hippocampal synaptic transmission. The endogenous opioid system (EOS) plays essential roles in stress-related emotional and physiological responses. Specifically, behavioral studies have shown that the impairment of memory retrieval induced by stressful events involves the activation of opioid receptors. However, it is unclear whether signaling mediated by μ-opioid receptors (μRs), one of the three major opioid receptors, participates in acute stress-related hippocampal LTD facilitation. Here, we examined the effects of a single elevated platform (EP) stress exposure on excitatory synaptic transmission and plasticity at the Schaffer collateral-commissural (SC) to CA1 synapses by recording electrically evoked field excitatory postsynaptic potentials and population spikes of hippocampal pyramidal neurons in anesthetized adult mice. EP stress exposure attenuated GABAergic feedforward and feedback inhibition of CA1 pyramidal neurons and facilitated low-frequency stimulation (LFS)-induced long-term depression (LTD) at SC-CA1 glutamatergic synapses. These effects were reproduced by exogenously activating μRs in unstressed mice. The specific deletion of μRs on GABAergic neurons (μRGABA) not only prevented the EP stress-induced memory impairment but also reversed the EP stress-induced attenuation of GABAergic inhibition and facilitation of LFS-LTD. Our results suggest that acute stress endogenously activates μRGABA to attenuate hippocampal GABAergic signaling, thereby facilitating LTD induction at excitatory synapses and eliciting memory impairments.